THE STUDY OF DECISION MAKING STYLE OF UNIVERSITY STUDENTS WHO DO SPORTS - Meric Eraslan; Gokhan Caliskan (European Scientific Journal, ESJ, 2014)
The purpose of this study is to determine decision-making strategies of hockey players according to some variables. 124 ice hockey players of 68 men and 56 women who have participated in the Inter-University Ice Hockey Tournament participated in the study. Decision Making Strategies Scale developed by Kuzgun (1993) was used to determine the strategies of decision making strategies of the participants. In the analysis of data obtained in SPSS 15.0 for Windows program, Mann Whitney U and Kruskal-Wallis H analysis was used. At the end of the study, it has been found that there is no significant difference on decision-making strategies of hockey players, according to the family income and family structure and gender of the athletes (p>0.05). In contrast, it has been determined that decision making strategies vary according to the number of siblings; athletes who have 1-3 siblings compared to the ones who have 4-6 siblings are higher in logical-systematic decision making strategies statistically (p < 0.05). Besides, it is also determined that ice hockey players who participated in the research logical - systematic decision making use impulsive decisionmaking, decision-making dependent on mid-level.